Two new species of the genus Nygmia Hübner, 1820 (Lepidoptera, Erebidae, Lymantriinae) from China - Ouyang, Si-Qi; Zhang, Tong; Yu, Xia; Pan, Zhaohui (Zootaxa, 2025)
Two new species of the genus Nygmia Hübner, 1820, Nygmia linzhiensis Pan & Ouyang, sp. nov. and Nygmia motuoensis Pan & Ouyang, sp. nov., are described. Adults and genitalia are illustrated.